Leading sectors and structural dynamics: an input-output analysis contrasting the BRICs growth paths - Magacho, Guilherme Riccioppo; Marconi, Nelson; Rocha, Igor (Brazilian Keynesian Review, 2019)
Although all the BRICs (Brazil, Russia, India and China) experienced a period of significant growth during the 2000s, their growth paths were far from homogenous. The growth path followed by Brazil and Russia was based on the production and export of primary goods, while in China and India the pattern of industrial development remained grounded in manufacturing exports and services, respectively. These distinct trajectories resulted in a vast range of interpretations about sectors that act as the relevant engines of growth. On the one hand, some economists supported the idea that expansion based on the production and export of commodities or services had no negative effect once these countries were exploiting their comparative advantages. Alternatively, the main argument of those who did not support economic growth based on primary product exports was that development is essentially a process of structural change, and sustained economic growth is associated with the capacity to diversify the structure of domestic production. With the aim of analyzing the different growth paths of the BRIC countries in recent decades and their long-term consequences, this study assessed the potential of each sector to promote economic growth. Input-output tables were used to calculate each sector’s output multipliers, Rasmussen-Hirschman backward and forward linkage indexes, and pure normalized backward and forward linkage indexes with the aim of assessing which sectoral orientation has a higher potential to stimulate the economy as a whole. The results show that manufacturing is the sector where the multipliers are the highest, while they are the lowest in agriculture and mineral commodities. The findings corroborate the hypothesis that having a dynamic manufacturing sector is essential to promote economic growth. Moreover, the results show that forward linkages are larger than backward linkages for services and that modern services present slightly larger forward linkages than those observed for traditional services. In that way, the hypothesis that the output of services depends on production in other sectors, and hence that a service-oriented strategy is linked to manufacturing production and exports, is reinforced.